Juvenile books in intercultural, media integrated literature lessons - Kuzminykh, Ksenia (Glottodidactica, 2018)
The article starts with a discussion of the essential theories of reading and focuses on different models of understanding. In the next step, based on fragments taken from a novel by M. Zusak, the article develops an integrative literary and language teaching model in intercultural school lessons of literature in a way which stimulates a highly functional analytical, receptive and productive handling of language semantics and performance. It demonstrates the combination of literature and film as a possibility for successful literary, language and media learning.